Discriminant analysis in evaluating the features of formation cumulative effect power loads in girls 7 years old - Mirosława Cieślicka; Olga Ivashchenko (Kazimierz Wielki University, 2017)
Purpose: To experimentally ground the technological approaches to evaluating training effects of primary schoolers' power loads. Material and methods: The participants in the study were 40 in girls 7 years old. To achieve the objectives outlined, the research used the following methods: analysis of scientific and methodological literature, pedagogical testing, modeling, pedagogical observation and experiment, methods of mathematical experiment planning (complete factorial experiment, 2k type), discriminant analysis. Results: The training pattern affects the dynamics in the test results for the second grade girls. The test results can improve provided that the power load brings about significant changes after the training at each spot, after the training (immediate training effect), and twenty four hours after the power load (delayed training effect). The higher the dynamics is for the immediate and delayed training effects, the more significant are the improved power tests results observed after as few as three lessons. Conclusions: The discriminant function can be used to classify the training effects of the girls 7 years old power loads.